The FRED for Cerebral Aneurysms of the Posterior Circulation: A Subgroup Analysis of the EuFRED Registry - Griessenauer, C. J.; Möhlenbruch, M. A.; Hendrix, P.; Ulfert, C.; Islak, C.; Sonnberger, M.; Engelhorn, Tobias; Müller-Thies-Broussalis, E.; Finkenzeller, T.; Holtmannspötter, M.; Buhk, J. H.; Reith, W.; et al. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Flow diversion for the posterior circulation remains a promising treatment option for selected posterior circulation aneurysms. The Flow-Redirection Intraluminal Device (FRED) system has not been previously assessed in a large cohort of patients with posterior circulation aneurysms. The purpose of the present study was to assess safety and efficacy of FRED in this location. MATERIALS AND METHODS: Consecutive patients with posterior circulation aneurysms treated at 8 centers participating in the European FRED study (EuFRED) between April 2012 and January 2019 were retrospectively reviewed. Complication and radiographic and functional outcomes were evaluated. RESULTS: Eighty-four patients (median age, 54 years) with 84 posterior circulation aneurysms were treated with the FRED. A total of 25 aneurysms (29.8%) had previously ruptured, even though most aneurysms were diagnosed incidentally (45.2%). The intradural vertebral artery was the most common location (50%), and saccular, the most common morphology (40.5%). The median size was 7 mm. There were 8 (9.5%) symptomatic thromboembolic and no hemorrhagic complications. Thromboembolic complications occurred mostly (90.9%) in nonsaccular aneurysms. On last follow-up at a median of 24 months, 78.2% of aneurysms were completely occluded. Functional outcome at a median of 27 months was favorable in 94% of patients. All mortalities occurred in patients with acute subarachnoid hemorrhage and its sequelae. CONCLUSIONS: The largest cohort of posterior circulation aneurysms treated with the FRED to date demonstrated favorable safety and efficacy profiles of the device for this indication. Treatment in the setting of acute subarachnoid hemorrhage was strongly related to mortality, regardless of whether procedural complications occurred.
CRIS-Team Scopus Importer:2020-04-28